Multicast support in network based mobility management: Current challenges and solutions - Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Abdullah, Azween; Mohd. Ramli, Huda Adibah (American Scientific Publishers, 2016)
Network based mobility management protocol can be termed as Proxy MIPv6 (PMIPv6). It is introduced as a unicast network based mobility management. Route optimization as well as context transfers approaches are some intra domain multicast support mechanisms in PMIPv6. As for inter domain multicast support mechanism on PMIPv6 domain, global mobility and load balancing are some of the approaches. Enabling multicast support mechanism in PMIPv6 is an important issue. This is because, it is an effective IP multicast communication. Moreover, nowadays application such as IPTV traffic densely populates IP multicast network concerning packet loss, service disruption time, and handover latency are at high priority. The objective of this paper is to quantitatively investigate and analyze intra and inter domain mechanisms for multicast support in PMIPv6. Using total number of signaling and handover latency as the analytical parameters, it also highlights the strengths, the limitations of these mechanisms. After analysis of the prevailing state of the art, an enhanced scheme has proposed in which both route optimization and context transfer techniques are integrated. The proposed scheme can brings entire benefits of the multicast service on PMIPv6 domain